Assessment of Groundwater Recharge and Discharge for Sustainable Development of Rangpur District in Bangladesh - AKTAR, MST. MARIAM; BEGUM, SYEDA FAHLIZA; BASHAR, KHAIRUL (Bangladesh Geoscience Journal, 2023)
Estimation of recharge to and discharge from the aquifer is a prime requisite for sustainable development and management of groundwater (GW) in any region. In this study, annual recharge and discharge of groundwater are assessed to evaluate the resource potentiality for groundwater development in Rangpur District. Analysis of bore logs and groundwater level (GWL) data reveal that a thick sandy aquifer with unconfined to semi-confined in nature is extended at shallow depth throughout the area. Groundwater recharge from rainfall is estimated using Water Level Fluctuation (WLF) and Rainfall Infiltration Factor (RIF) methods for both monsoon and non-monsoon seasons. The total estimated annual groundwater recharge is approximately 2409.4 Mm3 and 51% of this total are recharged from annual rainfall, 48% from irrigation return flow and 1% from other sources. For monsoon season the main source of the recharged GW is rainfall but for non-monsoon it is irrigation return flow. The estimated annual abstraction of groundwater from the aquifer for irrigation, domestic and municipal purposes is 1527.55 Mm3. Though the annual recharge to the aquifer is valued greater than the annual discharge of groundwater in the study area, due to rapid urbanization and increased abstraction of groundwater, a gradual depletion of maximum depth to GWL is observed in the central part of the Rangpur City Corporation area since 2017. The depletion rate is about 0.13 m/year. However, steady or increasing trend in elevation of the GWL is observed in the peripheral part of the study area. The availability of replenishable groundwater for further development is currently not a challenging issue but lack of proper management of this resource is a matter of concern and may cause of a threat to the aquifer environment for this area.